CAKES FROM GLUTEN-FREE COMPOSITE FLOUR BLENDS - Quinones, Renissa S (Journal of Agriculture and Technology Management, 2015)
People with celiac disease (CD) depend only to strict adherence to a gluten-free diet to maintain quality of life. This study aimed to determine the physico-chemical, bacteriological, organoleptic and physical properties of cakes using wheat flour (WF) and gluten-free composite flour blends (GFCFB) having different percentage composition of rice flour (RF), potato starch (PS), tapioca starch (TS), millet flour (MF), and corn flour (CF). The experimental design was laid out in the study with six treatments in three replications using CRD under controlled condition. The experimental samples were subjected to different laboratory analyses. Sensory evaluation revealed that there was a significant mean differences(p˂0.05) in odor, flavor, texture, taste attributes and general acceptability among treatments. Cakes from WF exhibited quality sensory attributes among treatments, however cakes fromT5 (GFCFB 5) had the highest sensory ratings compared to cakes made from other gluten-free flour blends. There was no significant difference was observed in color attribute among treatments. Utilizing available functional ingredients can produce cakes from gluten-free composite flours with comparable quality characteristics with the cakes from wheat flours. Cakes using GFCFB with milkfish spines meal were formulated and found very acceptable in all attributes. The continuous production for commercialization of these gluten-free bakery products is recommended.